Integrating electrical resistivity tomography and x-ray fluorescence for characterizing limestone in the Wapulaka Formation, Central Buton, Indonesia - Syamsuddin, Erfan; Maulana, Adi; Assegaf, Alimuddin Hamzah; Irfan, Ulva Ria (Brawijaya University, 2025)
The Wapulaka Formation in Central Buton, Indonesia, is a tectonically complex carbonate system characterized by heterogeneous lithologies, including limestones, dolostones, and marls. This study integrates Electrical Resistivity Tomography (ERT) and X-Ray Fluorescence (XRF) to map the subsurface distribution and geochemical characteristics of limestone in the formation. Electrical Resistivity Tomography (ERT) surveys were conducted along four profiles, covering a total length of 495 meters, with an electrode spacing of 5 meters to identify resistivity variations linked to lithological changes, fractures, and karst formations. The collected data were processed and inverted with Res2DInv software, applying topographic corrections to produce high-resolution 2D resistivity models. The limestone samples were examined with an Epsilon 4 XRF spectrometer to ascertain the elemental concentrations, particularly the CaO and MgO levels. Borehole data were used to validate ERT findings and provide a lithological perspective. The amalgamation of the ERT and XRF datasets demonstrate a robust correlation between resistivity and chemical composition. High-resistivity zones (>5000 ?m) are associated with significant, high-purity limestone characterized by elevated CaO and reduced MgO levels, while low-resistivity regions (<1000 ?m) signify eroded, porous, or clay-rich portions with increased MgO and diminished CaO content. The Mg/Ca ratio, obtained from XRF analysis, acts as an indicator of dolomitization, with higher ratios linked to decreased resistivity values. This technology facilitated the creation of a predictive model for limestone quality utilizing resistivity, enhancing resource assessments and selective mining efficacy. This study illustrates the efficacy of integrating geophysical and geochemical methods to delineate intricate carbonate systems, providing insights into subsurface heterogeneity, diagenetic processes, and resource availability.